THE ROLE OF THE NURSE IN THE CARE OF NEPHROLOGY PATIENTS AND THE IMPORTANCE OF TRAINING IN THIS FIELD - Bara, Rajmonda (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to observe the role of nursing in the care of nephrology patients and the importance of their training in this field.This study is a retrospective descriptive type.In this study included a total of 160 licensed nurses with an average age of 41.5 ± 12.63 years.The study was conducted in a period of 2013-2015 in several regional hospitals in the country.The data were analyzed and certain conclusions drawn by SPSS version 15.00.The value p